Efektivitas Insektisida Botani dari Daun Mimba dan Wedusan sebagai Pengendalian Kepik Penghisap Kakao - Wardati, Irma; Atmaja, Fama Rudi; Erawati, Dyah Nuning; Galushasti, Andarula (Politeknik Negeri Lampung, 2023)
The impact of cocoa fruit-sucking ladybugs (Helopeltis antonii Signoret) is getting higher, resulting in control by considering costs and abundant raw materials. The study aimed to ascertain the efficiency of botanical insecticides made from neem and wedusan as controllers and their effect on the behavior of cacao fruit-sucking ladybugs. The research was carried out from May to August 2021 in Petungombo Hamlet, Sepawon Village, Plosoklaten District, Kediri Regency. This study used a Randomize Block Design Non-Factorial with the factors tested including I0 (no insecticide), I1 (5% neem leaf botanical insecticide), I2 (10% wedusan leaf botanical insecticide), and I3 (neem leaf vegetable botanical combination 5% and 10% wedusan leaf botanical insecticide). Further testing uses the Least Significant Difference test with a level of 5%. The results showed that the insecticidal substances of neem leaves and botanical insecticides of wedusan leaves were effective against ladybugs sucking cocoa fruit pods with a value of Lethal Time Fifty. The results were the fastest with a combination of the two over 111 hours and significantly affected behavioral changes classified as very low to low changes.